ENDOTHELIAL FUNCTION CHANGES IN PRE- AND POST-MENOPAUSAL WOMEN WITH ARTERIAL HYPERTENSION - E. B. Prokofyeva; A. G. Avtandilov (Российский кардиологический журнал)
Aim. To assess the impact of climacteric disturbances in menopause on the dynamics of endothelial function among women with arterial hypertension (AH). Material and methods. The study included 129 women: 101 with elevated blood pressure (BP) levels and 28 without AH. All participants underwent echocardiography, 24-hour BP monitoring (BPM), brachial artery (BA) Doppler ultrasound, and reactive hyperemia test with nitroglycerine. The parameters of 24-hour BPM, left ventricular myocardial mass index, diastolic function, and endothelial function were analysed by age and the time of the climacteric disturbance development. Results. According to the 24-hour BPM results, examined women had Stage I–II AH. AH duration increased with age and reached 4,67±0,45 years for pre-menopausal women, 6,47±0,57 years for women in early menopause, and 12,48±0,94 years for women in late menopause. Left ventricular diastolic dysfunction was registered in all three groups; among women in late menopause, it was significantly more pronounced than among pre-menopausal women (p<0,05). Mean values of BA diameter were 3,88±0,07, 4,11±0,08, and 4,08±0,08 mm among women in pre-menopause, early menopause, and late menopause, respectively (p<0,05). The reactive hyperemia test demonstrated inadequate BA dilatation in 36,1%, 46,9%, and 60,6%, respectively.>< 0,05). The reactive hyperemia test demonstrated inadequate BA dilatation in 36,1%, 46,9%, and 60,6%, respectively. Conclusion. Endothelial dysfunction was more pronounced among women in late menopause, which supports the presence of the association between more severe vascular disturbances and menopause among hypertensive women, as well as suggests a post-menopausal increase in cardiovascular risk levels.